2015
DOI: 10.1002/2014ja020743
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate observations of traveling convection vortices associated with transient events at the magnetopause

Abstract: Traveling convection vortices (TCVs) are generally produced by field-aligned currents (FACs) at high latitudes associated with transient changes of the magnetopause. This paper presents multipoint conjugate observations of transient events at the magnetopause measured in space and on the ground. The transient events showing radial fluctuation of the magnetopause in association with sudden increases in solar wind dynamic pressure were detected by both the Time History of Events and Macroscale Interactions du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 67 publications
(126 reference statements)
1
44
0
Order By: Relevance
“…These perturbation FACs were superimposed on the preexisting NBZ current system due to the northward IMF B Z . The vertical ion convection patterns that formed in association with these perturbation FACs have similar physical properties to those of the TCVs (Clauer et al, ; Engebretson et al, ; Friis‐Christensen et al, ; Glassmeier & Heppner, ; Hönisch & Glassmeier, ; Kim et al, ; Lanzerotti et al, ; Zesta et al, ). They formed on the dayside, near 70° latitude, and propagated toward the nightside.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These perturbation FACs were superimposed on the preexisting NBZ current system due to the northward IMF B Z . The vertical ion convection patterns that formed in association with these perturbation FACs have similar physical properties to those of the TCVs (Clauer et al, ; Engebretson et al, ; Friis‐Christensen et al, ; Glassmeier & Heppner, ; Hönisch & Glassmeier, ; Kim et al, ; Lanzerotti et al, ; Zesta et al, ). They formed on the dayside, near 70° latitude, and propagated toward the nightside.…”
Section: Discussionmentioning
confidence: 88%
“…The TCVs are pairs of twin vortices that form on the dayside and propagate toward the nightside, together with the PI and MI FAC profiles, as shown in Yu and Ridley (), Fujita, Tanaka, Kikuchi, Fujimoto, and Itonaga (), and Ozturk et al (). Some theoretical and observational studies have also found the links between the TCVs to the twin magnetospheric vortices in the equatorial plane (Glassmeier & Heppner, ; Glassmeier, Hönisch, & Untiedt, ; Keiling et al, ; Kim et al, ; Slinker, Fedder, Hughes, et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…The companion paper by Kim et al [] reported that the TCV centers during Event 1 and Event 2 were 73.5° MLAT and 72.0° MLAT, respectively, and the latitude of the transient compression events observed by THEMIS coincided approximately with that of the TCV center. These locations are similar to the estimated wave source locations based on the ground data.…”
Section: Discussionmentioning
confidence: 99%
“…Spacecraft positions in the GSE X ‐ Y plane during Events 1 and 2 are illustrated in Figure [cf. Kim et al , , Figures 6c and 6f], in which the three THEMIS spacecraft were fortuitously located near the magnetopause. The bow shock locations are obtained using the static model by Fairfield [].…”
Section: Observationsmentioning
confidence: 99%
“…g. Global and regional maps and parameterizations of geomagnetic disturbances (and time derivatives) that drive ground-induced currents (e.g., Carter et al, 2016;Woodroffe et al, 2016). h. Interhemispheric comparisons of regional ULF wave activity (e.g., Kim et al, 2013Kim et al, , 2015Zesta et al, 2016), electrojet currents, and cusp and substorm phenomena, in order to understand the way energy from the solar wind is transmitted asymmetrically to Earth's high-latitude regions.…”
Section: Higher-level Data Productsmentioning
confidence: 99%